Patterns and outcomes of paediatric trauma at a tertiary teaching hospital in Kenya - Ndungu, Anthony Wainaina; Sun, Jared; Musau, Joan; Ndirangu, Eunice (African journal of emergency medicine (Print), 2019)
Trauma continues to be a major cause of morbidity and mortality especially in the paediatric population of low- and middle-income countries such as Kenya. The aim of this study was to establish the profile and outcomes of admitted paediatric trauma cases at the Aga Khan University Hospital, Nairobi.This retrospective, descriptive study involved a 12-month chart review (January 2016-December 2016). A total of 218 records were identified of which 144 were reviewed.Most injuries were amongst boys (65.3%) and the very young (mean age 6), occurred in private residences (42.4% homes, 25.7% residential institutions), were typically caused by falls (56.3%) or penetrating trauma (13.2%), mostly resulted in extremity fractures (45.8% closed, 4.9% open) and burn or head injuries (in infants and small children), and got very little or no pre-hospital care (51.4% no care). Additionally, children with burns, brain injuries, or poly-trauma had the longest hospital stays and highest rates of mortality. A more detailed description of the patterns and outcomes seen are included in the study.Paediatric injuries remain a major public health problem and contribute a substantial proportion of all paediatric surgical admissions at the Aga Khan University Hospital in Nairobi. Based on the patterns and outcomes seen in this study, we therefore recommend for Nairobi (and possibly Kenya) to establish greater supervision and safety measures for children; targeting safety interventions at all children but particularly at boys, the very young, at home and in residential buildings; building pre-hospital emergency care that can accommodate children; and equipping paediatric trauma hospitals to especially handle bony fractures, burns, head injuries, and poly-traumas. A bespoke trauma registry would benefit the hospital, and likely the country as a whole.
Keywords: openalex:import

Exploring gender differences in household food security and implications for climate change adaptation in East Africa - Silvestri, Silvia; Douxchamps, Sabine; Kristjanson, Patti; Foerch, W.; Radeny, Maren A.O.; Mutie, Jeniffer Ndungulu; Quirós, Carlos F.; Ndungu, Anthony; Ndiwa, Nicholas N.; Mango, Joash; Herrero, M.; Claessen, L.; et al. (2014)
Keywords: openalex:import